Morbidity profile among housekeeping workers in a tertiary care hospital, South India - Jose, Femina; Nisha, Catherin; Jerome, Kerline; Paul, Jini (International Journal Of Community Medicine And Public Health, 2019)
Background: Housekeeping staff play an important role in maintaining the health and hygiene in the hospitals. The International Labor Organization (ILO) estimates that more than 125 million workers are victims of occupational accidents and diseases in a single year. Each year an estimated 2.2 million men and women die from work related injuries and diseases and 160 million cases of new diseases arise globally. The objective of the study was to estimate the prevalence of existing morbidities among housekeeping workers at a tertiary care hospital in South India. Methods: A cross-sectional descriptive study was undertaken in a private tertiary care hospital in south India for a period of one year (2017 September – 2018 September). Housekeeping workers who had work experience of more than one year in the current work place were enrolled in the study (n=168). The health of the workers was assessed to pick up the prevalence of various morbidities. Results: In the study population majority 133 (79.2%) were females and most of them 117 (69.64%) were in the age group of 30-49 years. There was statistically significant difference between work tenure and hypertension and diabetes (p<0.05). The common morbidities found among the study population was dental carries 111 (66.0%), pallor 24 (14.0%) and musculoskeletal disorders 20 (11.9%). Conclusions: Periodic examination and immediate corrective measures are advisable to protect the health of employees at risk. Stress management principles can be implemented to enhance physical and mental health. There is need for safety training program for housekeeping workers in the hospital.